Evaluating the Effectiveness of Medical–Dental Integration to Close Preventive and Disease Management Care Gaps - Mosen, David M.; Banegas, Matthew P.; Dickerson, John F.; Fellows, Jeffrey L.; Pihlstrom, Daniel J.; Kershah, Hala M.; Scott, Jason L.; Keast, Erin M. (Frontiers in Dental Medicine, 2021)
Background: The integration of medical care into the dental setting has been shown to facilitate the closure of care gaps among patients with unmet needs. However, little is known about whether program effectiveness varies depending on whether the care gap is related to preventive care or disease management. Materials and Methods: We used a matched cohort study design to compare closure of care gaps between patients aged 65+ who received care at a Kaiser Permanente Northwest (KPNW) Medical–Dental Integration (MDI) clinic or a non-MDI dental clinic between June 1, 2018, and December 31, 2019. The KPNW MDI program focuses on closing 12 preventive (e.g., flu vaccines) and 11 disease management care gaps (e.g., HbA1c testing) within the dental setting. Using the multivariable logistic regression, we separately analyzed care gap closure rates (yes vs. no) for patients who were overdue for: (1) preventive services only (n = 1,611), (2) disease management services only (n = 538), or (3) both types of services (n = 429), analyzing closure of each care gap type separately. All data were obtained through the electronic health record of KPNW. Results: The MDI patients had significantly higher odds of closing preventive care gaps (OR = 1.51, 95% CI = 1.30–1.75) and disease management care gaps (OR = 1.65, 95% CI = 1.27–2.15) than the non-MDI patients when they only had care gaps of one type or the other. However, no significant association was found between MDI and care gap closure when patients were overdue for both care gap types. Conclusions: Patients with care gaps related to either preventive care or disease management who received dental care in an MDI clinic had higher odds of closing these care gaps, but we found no evidence that MDI was helpful for those with both types of care gaps. Practical Implications: MDI may be an effective model for facilitating the delivery of preventive and disease management services, mainly when patients are overdue for one type of these services. Future research should examine the impact of MDI on long-term health outcomes.